ChemInform Abstract: Dihydrobiphenylenes Through Ruthenium‐Catalyzed [2 + 2 + 2] Cycloadditions of ortho‐Alkenylarylacetylenes with Alkynes. Issue 32 (12th August 2014) - Garcia‐Rubin, Silvia; Gonzalez‐Rodriguez, Carlos; Garcia‐Yebra, Cristina; Varela, Jesus A.; Esteruelas, Miguel A.; Saa, Carlos
Abstract: The internal alkyne 1‐(hex‐1‐yn‐1‐yl)‐2‐vinylbenzene fails to dimerize.